Exploring the predictive power of impulsivity measures in predicting self-reported and informant-reported inpatient disruptive behaviors - Soe-Agnie, Sabrina (The journal of forensic psychiatry & psychology, 2021)
Impulsivity is strongly associated with aggression and antisocial conduct. Although self-report measures are a time-efficient means to assess impulsivity, they may be susceptible to socially desirable responding, particularly in forensic psychiatry. The current study aimed to investigate the predictive validity of three measures of impulsivity in predicting self- and informant-reported antisocial behavior: the Barratt Impulsiveness Scale, the Self-Centered Impulsivity scale of the Psychopathic Personality Inventory-Revised and the general Disinhibition factor of the Externalizing Spectrum Inventory. Next, the mediating role of a measure of self-deception, the Virtuous Responding scale, was examined in these associations. Participants (N = 94) were inpatients from addiction care and forensic psychiatry. Two regression analyses were conducted using self-reported antisocial behavior in the first, and informant-reported antisocial behavior in the second analysis as outcome variables. In addition, a mediated regression analysis was conducted, using the Virtuous Responding scale as a mediator. The impulsivity measures showed a substantially lower predictive validity when informant-reported behavior was predicted. The Virtuous Responding scale appeared to be unreliable in the current sample and showed no mediation effect. The results showed insufficient support for the predictive validity of the three measures of impulsivity. Alternative time-efficient assessments for impulsivity are needed, such as informant-based measures.